2007
DOI: 10.1158/1078-0432.ccr-07-1094
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Two Dosing Schedules of Vandetanib (ZD6474), an Inhibitor of Vascular Endothelial Growth Factor Receptor and Epidermal Growth Factor Receptor Signaling, in Combination with Irinotecan in a Human Colon Cancer Xenograft Model

Abstract: Purpose: This in vivo study was designed to determine the optimal doses and schedules of vandetanib, a dual epidermal growth factor receptor (EGFR)-vascular endothelial growth factor receptor tyrosine kinase inhibitor, in combination with irinotecan in a murine xenograft model of human colon cancer. Experimental Design: HT-29 tumor-bearing nude mice were treated with two doses of vandetanib (12.5 and 25 mg/kg/d) with or without irinotecan (100 mg/kg) using either sequential or concurrent schedules for 30 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 37 publications
7
33
0
Order By: Relevance
“…In particular, these treatment combinations resulted in a slow tumor growth rate during the 2 weeks of vandetanib administration. These results confirm an earlier study by Troiani et al, 26 in which vandetanib showed a correlation between this dosing schedule and enhanced EGFR and VEGFR signal inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, these treatment combinations resulted in a slow tumor growth rate during the 2 weeks of vandetanib administration. These results confirm an earlier study by Troiani et al, 26 in which vandetanib showed a correlation between this dosing schedule and enhanced EGFR and VEGFR signal inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…Troiani et al [72] show in a mouse model of CRC that the most responsive tumors showed the greatest decreases in IAUC, AUC and K trans , compared to vehicle treated tumors. In another study, Checkley et al [71] show a dose-dependent decrease in K trans and v e in a mouse model of prostate cancer reflecting decreases in vascular permeability and perfusion.…”
Section: Tumor Physiology and Microenvironment By Dce-mri Dw-mri Cementioning
confidence: 99%
“…Several preclinical and clinical studies have been conducted which show the utility of quantitative DCE-MRI endpoints to assess therapeutic efficacy and the antivascular activity of novel targeted agents [64][65][66][70][71][72][73]. Troiani et al [72] show in a mouse model of CRC that the most responsive tumors showed the greatest decreases in IAUC, AUC and K trans , compared to vehicle treated tumors.…”
Section: Tumor Physiology and Microenvironment By Dce-mri Dw-mri Cementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, antitumor response can be improved by combining axitinib with the chemotherapeutic prodrug cyclophosphamide despite a substantial decrease in tumor uptake of the active drug [62]. Antitumor activity is also enhanced in combination therapies with the antiangiogenic TKRI vandetanib under conditions where tumor blood flow and drug uptake are reduced [63]. Clearly, in these cases, the antiangiogenic TKRI may induce a direct antitumor response through angiogenesis inhibition-induced tumor cell starvation, which is independent of, but complementary to, the cytotoxic response to chemo/radiotherapy.…”
Section: Combining Antiangiogenic Compounds With Conventional Chemothmentioning
confidence: 99%